An assessment of the effects of manual energy and material haulage on the initial embodied environmental impact of residential buildings - Emmanuel Udomiaye; Ukpong Edidiong; Ikpa Ochea (Mehran University Research Journal of Engineering and Technology)
The energy inputs associated with all the stages of production of a building are known as initial embodied energy. These stages range from the mining of natural materials to manufacturing, transportation, and construction. . Inadequate local data in the formulation of climate change mitigation strategies have made studies on the effects of construction and transportation energy/emissions very significant. The study aims to appraise the impact of material haulage and site construction processes on the initial embodied energy and emission in the Nigerian context with the view of identifying the effects of manual labour and material haulage. The objectives are: to estimate the transportation energy, and site construction, and identify the percentage of energy from manual work. The study adopted a case study methodology using multiple case studies and integrated the international energy/emission protocol. Construction energy and carbon emissions accounted for 3.9% and 1.52% respectively. Manual energy was found to be significant with an average manual energy intensity for the study area at 9.5MJ/m2. Also, transportation energy accounted for 11.65% of the initial embodied energy and 6.95% of emissions. Thus, recommended sustainable haulage approaches such as the reduction and enforcement of age restrictions on imported used trucks from <15 years to <5 years.